2016
DOI: 10.7150/thno.15871
|View full text |Cite
|
Sign up to set email alerts
|

Simple, Sensitive and Accurate Multiplex Detection of Clinically Important Melanoma DNA Mutations in Circulating Tumour DNA with SERS Nanotags

Abstract: Sensitive and accurate identification of specific DNA mutations can influence clinical decisions. However accurate diagnosis from limiting samples such as circulating tumour DNA (ctDNA) is challenging. Current approaches based on fluorescence such as quantitative PCR (qPCR) and more recently, droplet digital PCR (ddPCR) have limitations in multiplex detection, sensitivity and the need for expensive specialized equipment. Herein we describe an assay capitalizing on the multiplexing and sensitivity benefits of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 38 publications
2
109
0
Order By: Relevance
“…The RAF dimers are subsequently disrupted by ERK-mediated feedback phosphorylation, which also disrupts the RAS-RAF interaction and attenuates RAF signaling. However, dimerization is not needed for the function of BRAF V600E which alone has a high catalytic activity 42, 43. In the current study, we observed that Vemurafenib could promote BRAF/CRAF dimerization causing paradoxical ERK activation in Vemurafenib-resistant DTC cells.…”
Section: Discussionsupporting
confidence: 44%
“…The RAF dimers are subsequently disrupted by ERK-mediated feedback phosphorylation, which also disrupts the RAS-RAF interaction and attenuates RAF signaling. However, dimerization is not needed for the function of BRAF V600E which alone has a high catalytic activity 42, 43. In the current study, we observed that Vemurafenib could promote BRAF/CRAF dimerization causing paradoxical ERK activation in Vemurafenib-resistant DTC cells.…”
Section: Discussionsupporting
confidence: 44%
“…Compared to real-time PCR, ddPCR is much more accurate and easier to perform; accordingly, it requires much more costly equipment and consumables [33]. …”
Section: Resultsmentioning
confidence: 99%
“…[129] Basically, generated PCR amplicons were tagged with biotin molecules and target-specific overhang hybridization sequences. For example, Wee et al incorporated the standard PCR assay with a multiplex SERS barcoding system for ultrasensitive detection of cancer DNA mutations (BRAF V600E, c-Kit L576P, and NRAS Q61K) in ctDNA from serum samples of melanoma patients.…”
Section: Nanotag-based Detectionmentioning
confidence: 99%